HEMOLYTIC SYSTEMS CONTAINING ANIONIC DETERGENTS - Ponder, Eric (The Rockefeller University Press, 1946)
1. The members of the homologous series of anionic detergents, the sodium salts of the sulfated straight chain alcohols with the general formula C(n)H(2n+1)·SO(3)·Na, are hemolytic, the lytic activity being at a maximum when the compound contains 14 carbon atoms in the chain. In systems in which lysis is comparatively rapid, the hemolytic effect increases with increasing pH, but in systems containing quantities of lysin near the asymptotic concentrations the pH dependence of the activity is reversed. The effect of temperature is principally one on the velocity constant of the lytic reaction, with smaller effects on the position of the asymptotes of the time-dilution curves and on their shape. 2. The quantities of the detergents which produce disk-sphere transformations are approximately one-tenth of those required to produce complete hemolysis. In most cases, the shape change occurs when there are too few detergent molecules present to cover the red cell surfaces with a monolayer. 3. Plasma inhibits the hemolytic action of these detergents, and, in the quantities in which they occur in plasma, lecithin, serum globulin, cholesterol, and serum albumin, produce inhibitory effects which increase in that order in systems containing the C-14 sulfate. It can be inferred from these inhibitory effects that the anionic detergents can form compounds or complexes with lipid, lipoprotein, and protein components of the red cell ultrastructure.